In the Fifth at Malory Towers - Enid Blyton
Games, lessons, quarrels and tricks all form part of a lively term, but the biggest event of all is the Fifth Form pantomime, written, acted and produced entirely by the girls. It generates a lot of fun, but also a surprising amount of trouble.